Reduction-bias-resistant stable dielectric material and preparation method thereof

By introducing specific components and processing processes into the MLCC dielectric material, a dense fine crystal structure is solved, and the dielectric constant and bias stability of the dielectric material are difficult to coexist under the reducing atmosphere, and a high-performance anti-reduction bias stable dielectric material is realized, which is suitable for the manufacturing of high-capacity MLCC.

CN120423873APending Publication Date: 2025-08-05TIANJIN UNIV

Patent Information

Application Number
CN202510654955.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-21
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

It is difficult for existing MLCC dielectric materials to take into account high dielectric constant and bias stability in a reducing atmosphere, resulting in large changes in capacitance with bias, affecting energy storage efficiency and signal transmission quality.

Method used

Barium titanate with a particle size of 100-150nm is used as the main material, silicon oxide and magnesium oxide are combined as sintering aids, and rare earth element oxide, manganese oxide and zirconium oxide are added as auxiliary components. Through reduction sintering and oxidation treatment, a dense fine crystal structure is formed, which inhibits Ti4+ reduction and phase transition and optimizes grain boundary distribution.

Benefits of technology

The dielectric constant is 1500~2000, the dielectric loss is less than 1%, the insulation resistivity is 1.19×1012, the capacity temperature change rate is <±15%, and the capacitance change rate is less than 8% under the 2kv/mm electric field. It meets the X7R capacitance and temperature characteristics, compatible with the nickel electrode co-firing process, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120423873A_ABST
    Figure CN120423873A_ABST
Patent Text Reader

Abstract

The invention provides an anti-reduction bias voltage stable type dielectric material. The dielectric material comprises a main body material, a sintering aid and auxiliary components, wherein the main body material comprises barium titanate with the particle size of 100-150nm, the sintering aids comprise silicon oxide and magnesium oxide, and the auxiliary components comprise oxides of rare earth elements, manganese oxide and zirconium oxide. On the other hand, the invention further provides a preparation method of the dielectric material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure belongs to the technical field of electronic materials, and in particular discloses a dielectric material that is stable against reduction bias and a preparation method thereof. Background Art

[0002] Multilayer ceramic capacitors (MLCCs) are key components in the electronic device market. Their higher capacitance density, miniaturized packaging, excellent temperature stability, and long life have made them indispensable passive components in mobile communications, automotive electronics, the Internet of Things, and high-density integrated circuits. The core structure of an MLCC consists of alternating layers of ceramic dielectric and internal electrodes. The dielectric properties of the ceramic dielectric material and the conductive characteristics of the internal electrodes directly determine the device's capacitance, reliability, and cost-effectiveness.

[0003] In related technologies, MLCCs typically use silver-palladium (Ag-Pd) alloys as internal electrode materials, but the high cost of precious metals limits their widespread adoption. To reduce production costs and improve performance, the industry has gradually shifted to base metal electrode (BME) technology, exemplified by nickel (Ni). However, Ni electrodes are susceptible to oxidation during high-temperature sintering, resulting in decreased conductivity and increased dielectric loss, necessitating co-firing in a reducing atmosphere. This process constraint places stringent demands on the corresponding ceramic dielectric material: the dielectric must maintain high density, a high dielectric constant (such as X7R dielectric), and excellent reduction resistance in a reducing atmosphere, while also requiring thin-layer processing capabilities to accommodate the design requirements of high-capacity MLCCs. Therefore, developing high-performance dielectric materials compatible with Ni electrodes has become a key technical bottleneck in promoting the development of higher-reliability MLCCs.

[0004] As MLCCs evolve toward ultra-thin dielectric layers (submicron-level) and higher operating voltages, the electric field strength per unit dielectric thickness increases dramatically, further exacerbating the nonlinear capacitance decay with bias voltage. These bias characteristic defects directly lead to reduced energy storage efficiency, high-frequency decoupling failure, and signal distortion in circuit applications, severely restricting the application of high-capacity MLCCs in high-density power modules and high-speed digital circuits. While existing technologies can partially mitigate bias sensitivity by optimizing dielectric composition (such as doping), achieving capacitance stability over a wide bias voltage range while maintaining a high dielectric constant is difficult.

[0005] Therefore, designing a dielectric material with good anti-bias performance and compatible with the nickel electrode preparation process has far-reaching practical significance. Summary of the Invention

[0006] In view of this, in order to solve at least one technical problem in related technologies and other aspects, the present disclosure proposes a dielectric material that is stable against reduction bias, including: a main material, a sintering aid, and auxiliary components; wherein the main material includes barium titanate with a particle size of 100-150nm, the sintering aid includes silicon oxide and magnesium oxide, and the auxiliary components include oxides of rare earth elements, manganese oxide, and zirconium oxide.

[0007] According to an embodiment of the present disclosure, the chemical formula of the dielectric material is [100-(x+y+z+w+i)]BaTiO3+xSiO2+yMgO+zRe2O3+wMnO2+iZrO2, wherein 0≤x≤1.5, 0≤y≤1.0, 0<z≤4.1, 0<w≤1.2, and 0<i≤0.5.

[0008] According to an embodiment of the present disclosure, the rare earth element includes at least one of dysprosium, holmium, and yttrium.

[0009] According to an embodiment of the present disclosure, based on the total molar fraction of the dielectric material, the molar fraction of the dysprosium element is 2 mol% to 6 mol%, the molar fraction of the holmium element is 0 to 2 mol%, the molar fraction of the yttrium element is 0.02 mol% to 0.08 mol%, the molar fraction of the manganese element in manganese oxide is 0 mol% to 1.2 mol%, and the molar fraction of the zirconium element in zirconium oxide is 0.2 mol% to 0.5 mol%.

[0010] According to an embodiment of the present disclosure, based on the total mole fraction of the dielectric material, the mole fraction of silicon oxide is 0 mol % to 1.5 mol %, and the mole fraction of magnesium oxide is 0 mol % to 1.0 mol %.

[0011] In another aspect of the present disclosure, a method for preparing the aforementioned dielectric material is also provided, comprising:

[0012] mixing the main material, the sintering aid and the auxiliary components to obtain a mixed powder;

[0013] After mixing the mixed powder with the binder, granulation is performed to obtain a precursor;

[0014] The precursor is sintered in a reducing atmosphere, and then the sintered precursor is oxidized to obtain a dielectric material.

[0015] According to an embodiment of the present disclosure, the aforementioned steps of mixing the mixed powder with the binder and then granulating the precursor include:

[0016] The mixed powder is placed on a sieve with a first mesh size, the mixed powder is mixed with a binder and placed on a sieve with a second mesh size, wherein the binder is paraffin and the addition amount of the binder is 3-7%.

[0017] According to an embodiment of the present disclosure, the sintering process includes: sintering the precursor at 1280-1330° C. for 2-4 hours in a nitrogen-hydrogen mixed atmosphere.

[0018] According to an embodiment of the present disclosure, the oxidation treatment includes: oxidizing the sintered precursor at 900-1100° C. for 2-4 hours in an atmosphere containing oxygen.

[0019] According to an embodiment of the present disclosure, the aforementioned preparation method further includes: coating a conductive silver paste on the surface of the dielectric material, and performing a silver sintering treatment at 800-900°C.

[0020] According to the embodiments of the present disclosure, the oxide of the rare earth element has trivalent ions, which is beneficial to fix the lattice oxygen and block the Ti 4+ →Ti 3+ The reduction path enables the dielectric material to maintain high stability in a reducing atmosphere; manganese ions (Mn 2 + / 3+ / 4+ ) with rare earth cations replacing Ti 4+ Ions will reduce the phase transition temperature and form a peak effect. 4+ Ions mainly replace Ti 4+ The lattice spacing and lattice constant increase, suppressing the dielectric Curie peak and improving the capacitance-temperature characteristics. Furthermore, magnesium oxide helps suppress grain coarsening, forming a dense, fine-grained structure, significantly reducing the formation of oxygen vacancies and increasing the resistivity of the dielectric material. Oxygen vacancies and magnesium ions synergistically regulate the grain boundary barrier, increasing grain boundary density, hindering ferroelectric domain reversal, improving electric field uniformity, suppressing field concentration, and effectively improving the bias characteristics of the dielectric material.

[0021] According to the embodiments of the present disclosure, the dielectric constant of the dielectric material proposed in the present disclosure is 1500-2000, the dielectric loss is less than 1%, and the insulation resistivity is 1.19×10 12 The capacitance temperature variation rate is <±15%, and under an electric field strength of 2kV / mm, the capacitance variation rate is less than 8%, making it a type of anti-reduction bias-stable dielectric material that meets the X7R capacitance-temperature characteristics. This disclosure, through the design of dielectric material components, makes the dielectric material compatible with the nickel electrode co-firing process, breaking through the bottleneck of traditional anti-reduction dielectric materials that struggle to coexist with capacitance-temperature characteristics and bias stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a flow chart of a method for preparing a dielectric material according to an embodiment of the present disclosure;

[0023] Figure 2 is a SEM image of the dielectric material prepared in Example 1 of the present disclosure;

[0024] Figure 3is a SEM image of the dielectric material prepared in Example 2 of the present disclosure;

[0025] Figure 4 is a SEM image of the dielectric material prepared in Example 3 of the present disclosure;

[0026] Figure 5 is a grain size distribution diagram of the dielectric material prepared in Example 1 of the present disclosure;

[0027] Figure 6 is a grain size distribution diagram of the dielectric material prepared in Example 2 of the present disclosure;

[0028] Figure 7 is a grain size distribution diagram of the dielectric material prepared in Example 3 of the present disclosure;

[0029] Figure 8 is a graph showing the change in dielectric constant and temperature of the dielectric material prepared in Example 1 of the present disclosure;

[0030] Figure 9 is a graph showing the change in dielectric constant and temperature of the dielectric material prepared in Example 2 of the present disclosure;

[0031] Figure 10 is a graph showing the change in dielectric constant and temperature of the dielectric material prepared in Example 3 of the present disclosure;

[0032] Figure 11 is a capacitance-temperature variation diagram of the dielectric material prepared in Example 1 of the present disclosure;

[0033] Figure 12 is a capacitance-temperature variation diagram of the dielectric material prepared in Example 2 of the present disclosure;

[0034] Figure 13 is a capacitance-temperature variation diagram of the dielectric material prepared in Example 3 of the present disclosure;

[0035] Figure 14 is a graph showing the change in dielectric constant and DC bias voltage of the dielectric material prepared in Example 1 of the present disclosure;

[0036] Figure 15 This is a graph showing the change in dielectric constant and DC bias voltage of the dielectric material prepared in Example 2 of the present disclosure;

[0037] Figure 16 3 is a graph showing the change in dielectric constant and DC bias voltage of the dielectric material prepared in Example 3 of the present disclosure. DETAILED DESCRIPTION

[0038] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings.

[0039] The endpoints of the ranges and any values disclosed in this disclosure are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed in this disclosure.

[0040] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise," "include," etc. used herein indicate the presence of the features, steps, operations, and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, or components.

[0041] All terms used herein (including technical and scientific terms) have the meanings commonly understood by those skilled in the art unless otherwise defined. It should be noted that the terms used herein should be interpreted as having a meaning consistent with the context of this specification and should not be interpreted in an idealized or overly rigid manner.

[0042] It should be noted that, unless otherwise defined, technical or scientific terms used in this disclosure should have the ordinary meanings understood by persons of ordinary skill in the art to which this disclosure belongs. Where references to "first," "second," or the like are used throughout this disclosure, such references are intended solely to distinguish similar objects and should not be construed as indicating or implying their relative importance, order of precedence, or implicitly specifying the quantity of the technical features being referred to. References to "first," "second," or the like should be understood to be interchangeable where appropriate.

[0043] In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the fact that ordinary technicians in this field can implement them. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by this disclosure.

[0044] Multilayer ceramic capacitors (MLCCs) using high-dielectric-constant ceramics as dielectrics, such as X7R MLCCs, experience a decrease in capacitance as the bias voltage increases when a DC bias voltage is applied. This characteristic is known as the DC bias characteristic, or simply the bias characteristic. The polarization behavior of dipoles within the dielectric ceramic is the primary source of the dielectric constant. When a DC bias is applied, the direction of the dipole polarization aligns with the direction of the electric field, causing the dielectric constant to decrease and the capacitance of the dielectric material to decrease. The bias characteristic is a key indicator of the reliability of the dielectric ceramics used in MLCCs. As MLCCs develop toward higher capacity and smaller sizes, the dielectric layer thickness becomes thinner, increasing the DC bias electric field strength that the dielectric must withstand per unit thickness, making the capacitance drop even more pronounced.

[0045] If MLCC cannot provide sufficient effective capacity in circuit applications, it will lead to adverse phenomena such as decreased energy storage capacity or increased impedance and poor decoupling effect. Therefore, the DC bias characteristics of MLCC have become a hot topic in this field.

[0046] In the process of realizing this disclosure, innovative solutions were explored from the perspectives of dielectric microstructure design and interface control. Specifically, using ultrafine barium titanate as the matrix, by introducing rare earth ions (+3 valence), metal oxides and magnesium (Mg) for coordinated control, a high-performance and highly reliable dielectric material with "anti-reduction-capacitance-temperature characteristics-DC bias stability" was designed: rare earth ions suppress Ti by capturing electrons. 4+ Reduction to Ti 3+ ; Improve the reduction resistance; Manganese ions (Mn 2+ / 3+ / 4+ ) replaces Ti 4+ Ions will reduce the phase transition temperature and form a peak effect. 4+ Ion substitution Ti 4+ The lattice spacing and lattice constant increase, the dielectric Curie peak is suppressed, and the capacitance-temperature characteristics are improved; Mg 2+ Ion doping reduces the oxygen vacancy concentration, refines the grains and optimizes the grain boundary distribution, reduces the electric field distortion, and thus simultaneously improves the DC bias stability and X7R capacitance-temperature characteristics of the anti-reduction dielectric material.

[0047] In one aspect of the present disclosure, a dielectric material that is stable against reduction bias is disclosed, comprising: a main material, a sintering aid, and auxiliary components; wherein the main material comprises barium titanate with a particle size of 100-150 nm, the sintering aid comprises silicon oxide and magnesium oxide, and the auxiliary components comprise oxides of rare earth elements, manganese oxide, and zirconium oxide.

[0048] According to the embodiments of the present disclosure, the oxide of the rare earth element has trivalent rare earth ions, which is beneficial to fix lattice oxygen and blocks the Ti 4+ →Ti 3+The reduction path enables the dielectric material to maintain high stability in a reducing atmosphere; manganese ions (Mn 2+ / 3+ / 4+ ) replaces Ti 4+ Ions will reduce the phase transition temperature and form a peak effect. 4+ Ions mainly replace Ti 4+ The lattice spacing and lattice constant increase, suppressing the dielectric Curieli peak and improving the capacitance-temperature characteristics. Magnesium oxide helps inhibit grain coarsening, forming a dense, fine-grained structure, significantly reducing the formation of oxygen vacancies and increasing the resistivity of the dielectric material. Oxygen vacancies and magnesium ions synergistically regulate the grain boundary barrier, increasing the grain boundary density, reducing the local concentration of the electric field, and effectively improving the bias characteristics of the dielectric material.

[0049] According to the embodiments of the present disclosure, the dielectric constant of the dielectric material proposed in the present disclosure is 1500-2000, the dielectric loss is less than 1%, and the insulation resistivity is 1.19×10 12 The capacitance temperature variation rate is <±15%, and under an electric field strength of 2kV / mm, the capacitance variation rate is less than 8%, making it a type of anti-reduction bias-stable dielectric material that meets the X7R capacitance-temperature characteristics. This disclosure, through the design of dielectric material components, makes the dielectric material compatible with the nickel electrode co-firing process, breaking through the bottleneck of traditional anti-reduction dielectrics that struggle to balance dielectric constant and bias stability.

[0050] Specifically, in the dielectric material proposed in the present disclosure that takes into account both anti-reduction performance and bias stability, the main material is barium titanate with a particle size of 100-150nm. The nano-scale grains are conducive to suppressing domain wall migration, reducing polarization hysteresis under DC bias, improving capacitance attenuation problems, and providing basic support for the coexistence of high dielectric constant and bias stability. Barium titanate powder within this particle size range is conducive to improving the DC bias and capacitance-temperature characteristics of the dielectric material while ensuring the miniaturization and anti-reduction of MLCC. The main barium titanate material accounts for 91.54 to 93.74 mol% of the total mass of the dielectric material.

[0051] Specifically, in the dielectric material proposed in the present disclosure that takes into account both anti-reduction performance and bias stability, silicon oxide, as a sintering aid, can form a eutectic phase with other components during high-temperature sintering, reduce the sintering temperature through liquid phase generation, promote liquid phase diffusion and rearrangement between particles, and thus improve the density of the dielectric material; at the same time, molten silicon oxide can partially fill the pores at the grain boundaries, optimize the grain boundary structure, reduce the defect density at the grain boundaries, and enhance the mechanical strength and insulation performance of the material. Magnesium oxide, which is also a sintering aid, on the one hand inhibits the formation of oxygen vacancies. The reduction of oxygen vacancies reduces the free carrier concentration and significantly improves the insulation resistivity of the dielectric material; on the other hand, MgO 2+During the sintering process, ions tend to segregate to the grain boundaries, suppressing excessive grain growth by pinning grain boundary migration and forming a fine-grained structure. Grain refinement increases the density of grain boundaries per unit volume. Grain boundaries act as potential barriers, hindering charge migration and further reducing leakage current. The fine-grained structure makes the electric field distribution more uniform, reducing local electric field concentration. At the same time, the high-density grain boundaries disperse polarized charge accumulation, alleviating the nonlinear decay of the dielectric constant under DC bias, thereby significantly improving the bias stability of the dielectric material.

[0052] Specifically, in the dielectric material proposed in the present disclosure that takes into account both anti-reduction performance and bias stability, the rare earth ions provided by the rare earth element oxide can capture electrons in a reducing atmosphere and have high oxygen affinity, which can anchor lattice oxygen, inhibit the desorption of oxygen in a high-temperature reducing atmosphere, and reduce the generation of oxygen vacancies. The reduction of oxygen vacancies directly inhibits the Ti 3+ The production of this material significantly improves the reliability of dielectric materials in a reducing sintering environment.

[0053] According to an embodiment of the present disclosure, the chemical formula of the dielectric material is [100-(x+y+z+w+i)]BaTiO3+xSiO2+yMgO+zRe2O3+wMnO2+iZrO2, wherein 0≤x≤1.5, 0≤y≤1.0, 0<z≤4.1, 0<w≤1.2, and 0<i≤0.5.

[0054] According to the embodiments of the present disclosure, the dielectric material designed by the present disclosure comprehensively controls the values of x, y, z, w, and i to determine the content of sintering aids and auxiliary components, so as to achieve the purpose of synthesizing a dielectric material that is stable against reduction bias by adjusting the stoichiometric ratio, thereby achieving the purpose of comprehensive control reliability.

[0055] According to an embodiment of the present disclosure, the rare earth element includes at least one of dysprosium, holmium, and yttrium.

[0056] According to an embodiment of the present disclosure, based on the total molar fraction of the dielectric material, the molar fraction of the dysprosium element is 2 mol% to 6 mol%, the molar fraction of the holmium element is 0 to 2 mol%, the molar fraction of the yttrium element is 0.02 mol% to 0.08 mol%, the molar fraction of the manganese element in manganese oxide is 0 mol% to 1.2 mol%, and the molar fraction of the zirconium element in zirconium oxide is 0.2 mol% to 0.5 mol%.

[0057] According to the embodiments of the present disclosure, rare earth oxides introduce electron traps through acceptor doping, actively capture free electrons in a reducing atmosphere, and block the Ti 4+ →Ti 3+ The reduction path of MgO is suppressed, and the formation of oxygen vacancies is inhibited, thereby significantly improving the anti-reduction properties of the dielectric material. 2+The synergistic effects of ions on oxygen vacancy suppression and grain refinement ensure the material's higher insulation and DC bias stability under reducing processes.

[0058] According to an embodiment of the present disclosure, based on the total mole fraction of the dielectric material, the mole fraction of silicon oxide is 0 mol % to 1.5 mol %, and the mole fraction of magnesium oxide is 0 mol % to 1.0 mol %.

[0059] Figure 1 It is a flow chart of the method for preparing the dielectric material in the embodiment of the present disclosure.

[0060] In another aspect of the present disclosure, a method for preparing the aforementioned dielectric material is also proposed, such as Figure 1 As shown, the following steps S101 to S103 are included:

[0061] Step S101: mixing the main material, sintering aid and auxiliary components to obtain a mixed powder;

[0062] Step S102: mixing the mixed powder with the binder and granulating the mixture to obtain a precursor;

[0063] Step S103: sintering the precursor in a reducing atmosphere, and then oxidizing the sintered precursor to obtain a dielectric material.

[0064] According to the embodiments of the present disclosure, the main material (barium titanate), sintering aids (silicon oxide, magnesium oxide) and auxiliary components (rare earth elements and oxides of manganese and zirconium) are first mixed to ensure uniform dispersion, avoiding local component segregation, and laying the foundation for grain boundary control and defect suppression in subsequent sintering. Sintering in a reducing atmosphere can protect the nickel (Ni) internal electrode from oxidation, while relying on the synergistic effect of the sintering aid and auxiliary components to maintain the chemical stability of the dielectric material and avoid Ti caused by the reducing atmosphere. 3+ After sintering, the material undergoes an oxidation treatment and controlled oxygen partial pressure annealing to partially fill the oxygen vacancies generated during the sintering process, restoring the lattice oxygen balance, further improving the dielectric material's insulation resistivity and reducing leakage current. This method is compatible with existing MLCC base metal electrode (BME) processes and features a simple preparation method, a short preparation cycle, and a large single-shot preparation volume, making it easy to promote large-scale production without the need for special equipment. Furthermore, by optimizing the sintering and oxidation steps, it reduces energy consumption and production costs while maintaining material performance, making it suitable for large-scale production.

[0065] In some specific embodiments, in step S101, the main material, sintering aid, and auxiliary components are mixed, wet ball milled, dispersed, and then dried to obtain a ceramic powder. More specifically, the wet ball milling process includes using 5 mm zirconium dioxide balls as the milling medium, isopropyl alcohol as the solvent, and a milling time of 10 to 15 hours.

[0066] According to an embodiment of the present disclosure, the aforementioned steps of mixing the mixed powder with the binder and then granulating the precursor include: placing the mixed powder into a sieve with a first mesh size (for example, a 40-mesh sieve), mixing the mixed powder with the binder and placing the mixed powder into a sieve with a second mesh size (for example, an 80-mesh sieve), wherein the binder is paraffin wax and the amount of the binder added is 3-7%.

[0067] In some specific embodiments, in step S102, the mixed powder is granulated and dry-pressed to obtain a precursor, which is then placed in an air atmosphere for debinding. More specifically, the dried mixed powder is passed through a 40-mesh sieve, and 3-7 wt% paraffin wax (e.g., 5%) is added as a binder and mixed with the mixed powder in an evaporating dish. After the well-mixed mixed powder cools, it is passed through an 80-mesh sieve to obtain a well-granulated mixed powder. The mixed powder is then pressed into a precursor green body with a thickness of approximately 1 mm and a diameter of approximately 10 mm using a 10 mm diameter mold under an external pressure of 7 MPa.

[0068] According to an embodiment of the present disclosure, the sintering process includes: sintering the precursor at 1280-1330° C. for 2-4 hours in a nitrogen-hydrogen mixed atmosphere (eg, 0.1% H 2 / N 2 ).

[0069] According to the embodiments of the present disclosure, the sintering conditions meet the co-firing requirements of nickel electrodes, eliminating the need for complex atmosphere control equipment and reducing production costs. Through the coordinated optimization of temperature, atmosphere, and time, high densification and a fine-grained structure of the dielectric material are achieved while also taking into account the protection and anti-reduction properties of the nickel electrode. The result is an MLCC dielectric material with a high dielectric constant, low dielectric loss, excellent bias stability, and high reliability.

[0070] According to an embodiment of the present disclosure, the oxidation treatment includes: oxidizing the sintered precursor at 900-1100° C. for 2-4 hours in an atmosphere containing oxygen.

[0071] According to the embodiments of the present disclosure, 900-1100°C is lower than the sintering temperature of barium titanate, preventing secondary grain growth or structural collapse while ensuring a sufficiently high oxygen diffusion rate for effective repair. A holding time of 2-4 hours ensures that oxygen atoms fully penetrate the interior of the structure and the grain boundaries, avoiding incomplete oxidation due to a short holding time or component volatilization due to a long holding time. This oxidation treatment effectively compensates for the negative effects of reductive sintering on the dielectric material by repairing oxygen vacancies, passivating grain boundaries, and eliminating defects, achieving a comprehensive improvement in the electrical performance and reliability of the dielectric layer.

[0072] More specifically, through the collaborative design of "reduction sintering + oxidation post-treatment", while being compatible with the nickel electrode co-firing process, the negative impact of the reducing atmosphere on the dielectric material (such as Ti3+ The material is then processed through oxidation post-treatment to repair microscopic defects, ultimately achieving the combined performance of higher dielectric constant, low dielectric loss, high insulation and excellent bias stability, meeting the stringent requirements of high-capacity MLCC for dielectric materials.

[0073] According to an embodiment of the present disclosure, the aforementioned preparation method further includes step S104: coating a conductive silver paste on the surface of the dielectric material, and performing a silver sintering treatment at 800-900°C.

[0074] In some specific embodiments, the conductive silver paste is uniformly coated on the surface of the dielectric material and then co-fired at a co-firing temperature of 850°C.

[0075] According to the embodiments of the present disclosure, the dielectric material prepared by the present disclosure has low cost, does not contain harmful elements, and is suitable for alkali metal Ni to replace precious metals such as Pb and Ag as the internal electrode of MLCC, which greatly reduces the cost of MLCC.

[0076] It should be noted that the embodiments described are only part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, other embodiments obtained by ordinary technicians in this field without making creative work are all within the scope of protection of the present disclosure.

[0077] Examples 1-3

[0078] The main material, sintering aid, and auxiliary ingredients in varying proportions were mixed, weighed, and loaded into a ball mill. Milling media and grinding balls were then added and uniformly mixed in a ball mill to produce a mixed powder. The specific component proportions of Examples 1, 2, and 3 are shown in Tables 1, 2, and 3 below. In this example, deionized water was used as the milling media, and the mass ratio of grinding balls, mixed powder, and deionized water was approximately 1:1:1. The milling speed was set at 400 rpm.

[0079] 7wt% paraffin wax is added as a binder and mixed with the powder mixture in an evaporating dish to improve the powder's fluidity and plasticity. After cooling, the well-mixed powder mixture is passed through an 80-mesh sieve to obtain a well-granulated mixed powder. The granulated mixed powder is then pressed into a preformed green body using a mold under external pressure. The binder removal curve is set as follows: room temperature for 3.5 hours, then 550°C, and then 2 hours, then 550°C. A slow temperature increase prevents the formation of numerous pores within the green body.

[0080] The content and flow rate of the sintering atmosphere were adjusted by the gas mixing system. Reduction treatment was carried out under the protection of an N2 atmosphere containing O2, and then oxidation was performed for 2 hours. For the specific sintering process, please refer to Table 4 below.

[0081] Table 1: Component ratio of the mixed powder in Example 1

[0082]

[0083] Table 2: Component ratio of the mixed powder in Example 2

[0084]

[0085] Table 3: Component ratio of the mixed powder in Example 1

[0086]

[0087] Table 4: Sintering process table

[0088]

[0089] The dielectric materials prepared in Examples 1-3 were subjected to surface morphology and performance testing. To test the dielectric properties of the samples, conductive silver paste was evenly coated on both surfaces and then placed in a box-type resistance furnace for "burn-in" of the silver paste. The burn-in temperature was set at 840°C, the heating rate was 5°C / min, and the holding time was 10 minutes. The test results are recorded in Tables 5, 6, and 7 below.

[0090] Table 5: Performance test table of dielectric materials in Example 1

[0091]

[0092] Table 6: Performance test table of dielectric materials in Example 2

[0093]

[0094] Table 7: Performance test table of dielectric materials in Example 3

[0095]

[0096] Figure 2 、 3 4 are SEM images of the dielectric materials prepared in Examples 1, 2, and 3 of the present disclosure, respectively. Figure 5 、 6 , 7 are grain size distribution diagrams of the dielectric materials prepared in Examples 1, 2, and 3 of the present disclosure, respectively.

[0097] like Figure 2 、 3As shown in Figures 4 and 5, the dielectric materials prepared in Examples 1, 2, and 3 of the present disclosure have uniform grain sizes, smooth particle surfaces, and no cracks. The particle size of the BaTiO3 powder, the main material, in Examples 1, 2, and 3 is all 150 nm. However, the average particle sizes of the dielectric materials prepared in Examples 1, 2, and 3 are 755 nm, 266 nm, and 212 nm, respectively. This may be because the higher the amount of magnesium oxide added, the smaller the average particle size.

[0098] Figure 8 、 9 10 are the dielectric constant and temperature variation diagrams of the dielectric materials prepared in Examples 1, 2, and 3 of the present disclosure, respectively. Figure 11 、 12 1 and 13 are the capacitance-temperature variation diagrams of the dielectric materials prepared in Examples 1, 2, and 3 of the present disclosure, respectively. Figure 14 、 15 1 and 16 are respectively diagrams showing the dielectric constant and DC bias change of the dielectric materials prepared in Examples 1, 2, and 3 of the present disclosure.

[0099] like Figure 8-16 As shown in Tables 5-7, the dielectric constant of the dielectric material proposed in this disclosure is 1500-2000, the dielectric loss is less than 1%, and the insulation resistivity can reach 1.19×10 12 The capacitance temperature variation is <±15%, and the dielectric constant variation is less than 8% at an electric field strength of 2kV / mm, making it a type of dielectric material that meets the X7R capacitance-temperature characteristics and is stable against reduction bias. Furthermore, smaller dielectric grain sizes exhibit improved bias resistance, demonstrating that increasing grain boundary density optimizes electric field distribution, avoids excessive local field strength, suppresses ferroelectric domain wall migration, and effectively improves the bias stability of the dielectric material.

[0100] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present disclosure. It should be understood that the above are only specific embodiments of the present disclosure and are not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the scope of protection of the present disclosure.

Claims

1. A dielectric material that is stable against reduction bias, comprising: Main material, sintering aid and auxiliary components; among them, The main material includes barium titanate with a particle size of 100-150 nm, the sintering aid includes silicon oxide and magnesium oxide, and the auxiliary components include oxides of rare earth elements, manganese oxide, and zirconium oxide.

2. The dielectric material according to claim 1, wherein The chemical formula of the dielectric material is [100-(x+y+z+w+i)]BaTiO3+xSiO2+yMgO+zRe2O3+wMnO2+iZrO2, wherein 0≤x≤1.5, 0≤y≤1.0, 0<z≤4.1, 0<w≤1.2, and 0<i≤0.

5.

3. The dielectric material according to claim 1, wherein The rare earth element includes at least one of dysprosium, holmium and yttrium.

4. The dielectric material according to claim 3, wherein Based on the total mole fraction of the dielectric material, the mole fraction of the dysprosium element is 2 mol% to 6 mol%, the mole fraction of the holmium element is 0 to 2 mol%, the mole fraction of the yttrium element is 0.02 mol% to 0.08 mol%, the mole fraction of the manganese element in the manganese oxide is 0 mol% to 1.2 mol%, and the mole fraction of the zirconium element in the zirconium oxide is 0.2 mol% to 0.5 mol%.

5. The dielectric material according to claim 1, wherein Based on the total mole fraction of the dielectric material, the mole fraction of the silicon oxide is 0 mol % to 1.5 mol %, and the mole fraction of the magnesium oxide is 0 mol % to 1.0 mol %.

6. A method for preparing the dielectric material according to any one of claims 1 to 5, comprising: Mixing the main material, sintering aid and auxiliary components to obtain a mixed powder; After mixing the mixed powder with a binder, granulating to obtain a precursor; The precursor is sintered in a reducing atmosphere, and then the sintered precursor is oxidized to obtain a dielectric material.

7. The method according to claim 6, wherein: The process of mixing the mixed powder with the binder and then granulating the precursor comprises: The mixed powder is placed on a sieve with a first mesh size, the mixed powder is mixed with a binder and placed on a sieve with a second mesh size, wherein the binder is paraffin and the addition amount of the binder is 3-7%.

8. The method according to claim 6, wherein: The sintering process includes: The precursor is sintered at 1280-1330° C. for 2-4 hours in a nitrogen-hydrogen mixed atmosphere.

9. The method according to claim 6, wherein: The oxidation treatment comprises: The sintered precursor is oxidized in an oxygen-containing atmosphere at 900-1100° C. for 2-4 hours.

10. The method according to claim 6, further comprising: The conductive silver paste is coated on the surface of the dielectric material, and silver sintering treatment is performed at 800-900°C.

Citation Information

Patent Citations

  • Anti-reduction X7R type superfine ceramic material and preparation method thereof

    CN117923892A

  • Medium material for MLCC and preparation method and application thereof

    CN118652115A

  • Co-doped barium titanate ceramic dielectric material as well as preparation method and application thereof

    CN118930251A

Cited By

  • Defect layer coated anti-reduction nano barium titanate-based ceramic and preparation method thereof

    CN122212729A